Technological properties of sour cassava starches: Effect of fermentation and drying processes - Diaz, Andrea (2018)
Cassava sour starch is a naturally-fermented, sun-dried product. It allows obtaining less dense bakery productsthan the native starch, being an appreciated gluten-free ingredient. The aim of this work was to study the effectof fermentation and drying method on the physicochemical and technological characteristics of cassava sourstarch and to identify the relationships among those distinctive features that may condition their potential foodapplications.Natural fermentation following starch extraction could not be replaced by the use of a starter. Sour starchespastes showed lower apparent viscosities related to their lactic and/or butyric acid content, and a higher retrogradationtendency, mainly associated to sun-drying. The fermentation combined with the solar expositionrepresent a complex process that induce changes not easily observed on starch powders but clearly evidencedafter gelatinization of the starch suspensions.